Bálint's syndrome, object seeing, and spatial perception - French, Craig (Wiley, 2018)
Ordinary cases of object seeing involve the visual perception of space and spatial location. But does seeing an object require such spatial perception? An empirical challenge to the idea that it does comes from reflection upon Bálint's syndrome, for some suppose that in Bálint's syndrome subjects can see objects without seeing space or spatial location. In this article, I question whether the empirical evidence available to us adequately supports this understanding of Bálint's syndrome, and explain how the aforementioned empirical challenge can be resisted.